Journal Portfolio Analysis for Countries, Cities, and Organizations: Maps and Comparisons - Leydesdorff, Loet; Heimeriks, Gaston; Rotolo, Daniele (Wiley, 2016)
Using Web-of-Science data, portfolio analysis in terms of journal coverage can be projected on a base map for units of analysis such as countries, cities, universities, and firms. The units of analysis under study can be compared statistically across the 10,000+ journals. The interdisciplinarity of the portfolios is measured using Rao-Stirling diversity or Zhang et al.'s (in press) improved measure 2D3. At the country level we find regional differentiation (e.g., Latin-American or Asian countries), but also a major divide between advanced and less-developed countries. Israel and Israeli cities outperform other nations and cities in terms of diversity. Universities appear to be specifically related to firms when a number of these units are exploratively compared. The instrument is relatively simple and straightforward, and one can generalize the application to any document set retrieved from WoS. Further instruction is provided online at http://www.leydesdorff.net/portfolio .
Keywords: cs.DL; Taverne